STRATEGIES OF RUSSIAN VERTICALLY INTEGRATED OIL COMPANIES IN THE GLOBAL MARKET - V. I. Golomedov (Vestnik MGIMO-Universiteta)
In this artıcle the analysis of the main directions of the strategic development of Russian vertically integrated oil companies is made including international expansion and development of relations with foreign partners and investors, mergers and aquisitions policy, global technology and qualified employees exchange, investments into research and development. Development of the global market brings processes of vertical integration to the international level, therefore one of the most urgent challenges facing the modern Russian vertically integrated oil companies is development of the new optimized strategy corresponding to global challenges and national priorities. The main strategic development’s directions of the Russian vertically integrated oil companies are described. For the companies accumulated significant financial resources, the priority is to actively enter the global market and to create the formation of transnational structures, which is due not only to the factors of globalization, but with very low efficiency and security of investments in the energy sector of Russia. The new strategy should promote increase the volume of oil production and petroleum products. Creation of vertically integrated companies leads to effective distribution of the factors of economic globalization. Instead of classic advantage factors comes global competitive advantages. First of all it is the ability to effectively distribute in time and place factors of economic activity using their advantage caused by their mobility. International expansion of Russian vertically integrated oil companies diversifies risks and makes the companies more sustainable. Futher diversification and integration of Russian companies is expected both In straight and reverse directions. Applying the strategy of vertical integration provides effective economic activity with high investment return.